The Atlas School of Islamic History during the 4th century AH-10 AD From emergence to decline - khalfat, Kamal (The Algerian Historical Journal, 2026)
This article deals with the emergence and development of the Atlas of the History of Islam school and the efforts made by its pioneers in order to provide very important images, maps and information about the Kingdom of Dar al-Islam during the second half of the fourth century AH and the tenth century AD, and so that the researcher in economic, social and political history to form a general picture of the resources of the major countries in Dar al-Islam, the source of trade exchanges, and the vitality of the countryside and cities, which are often explicit and clear texts for the human geography researcher. This study also aims to try to identify the methodology and objectives followed by the pioneers of this school in their codification, in order to reach the goals they sought to achieve either on the political or economic level until its demise.